Environmental Learning Experience Development for Elementary Students - Rakthai, Saksri (Naresuan University Journal: Science and Technology (NUJST); Vol 25 No 4 (2017): October - December 2017, 2017)
Environment was a significant problem in every country because every life was affected by environmental impact. Nowadays, there were many ways to solve these problems, especially, education. Education was the best solution to solve environmental problem by changing human attitude and behavior toward the environment.  The Objectives of this research were 1) to synthesize suitable environmental contents from the basic education core curriculum B.E. 2551 of Thailand for elementary students, and 2) to design Environmental Learning Experiences for elementary students. The samples were 30 elementary students from 6 schools located alongside of Damnoen Saduak canal. Suitable environmental contents were synthesized by focus group with 6 local environmental experts. Environmental Learning Experiences were assigned by researchers. The results showed that, the suitable local environmental contents for elementary students were 5 water quality indicators of the Damnoen Saduak canal as follows: (1) fish, (2) seaweed and water hyacinth, (3) nitrate, (4) dissolve oxygen, and (5) odor color and turbidity of water. The Environmental Learning Experiences were 7 learning stations. The evaluation of Environmental Learning Experience revealed that every students answered and practiced correctly 100 percent and the extracurricular experts thought that this Environmental Learning Experience was appropriate for elementary students due to: (1) appropriate location, (2) appropriate content and objective, (3) dividing group by mixing school, (4) one caretaker for each group, (5) fun activities, (6) gaming and answering in learning situation, and (7) suitable environmental contents arrangement. In addition, this research process could be developed to provide local curriculum for local schools around study area. Keywords: Environmental Learning Experiences, Development, Elementary Students
Keywords: Environmental Learning Experiences; Development; Elementary Students